2001
DOI: 10.1103/physrevlett.87.026401
|View full text |Cite
|
Sign up to set email alerts
|

Screening Breakdown on the Route toward the Metal-Insulator Transition in Modulation Doped Si/SiGe Quantum Wells

Abstract: Exploiting the spin resonance of a two-dimensional (2D) electron in SiGe͞Si quantum wells, we determine the carrier density dependence of the magnetic susceptibility. Assuming weak interaction, we evaluate the density of states at the Fermi level, D͑E F ͒, and the screening wave vector, q TF . Instead of the constant values of an ideal 2D system, we observe a gradual decrease towards the band edge. Calculating the mobility from q TF yields good agreement with experimental values justifying the approach. The de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 26 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…Previous experimental studies also reported similar exponents. 24,25 Low-density corrections to the RPA method have been suggested to explain this stronger dependence of the mobility upon the density. Indeed, if one goes beyond the TABLE I. Extracted power-law exponents α for heterostructures with different 2DEG depth in the lower and higher density regimes, along with Dingle ratios.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental studies also reported similar exponents. 24,25 Low-density corrections to the RPA method have been suggested to explain this stronger dependence of the mobility upon the density. Indeed, if one goes beyond the TABLE I. Extracted power-law exponents α for heterostructures with different 2DEG depth in the lower and higher density regimes, along with Dingle ratios.…”
mentioning
confidence: 99%
“…A common approach to experimentally determine the dominant scattering mechanisms in two-dimensional systems is to extract the power-law exponent from the density dependence of the mobility. Several experimental and theoretical studies have used similar techniques to analyze disorder in GaAs/AlGaAs structures, [15][16][17][18][19][20][21] Si MOSFETs, 22 and doped 4,[23][24][25] and undoped [26][27][28] Si/SiGe heterostructures. With this in mind, we present in this work a systematic study of the depth dependence of scattering mechanisms in undoped shallow Si/SiGe quantum wells with channel depth ranging from 100 nm to only 10 nm away from the surface, the shallowest Si/SiGe device reported to date.…”
mentioning
confidence: 99%
“…A large amplitude of the signal and a strong dependence of the amplitude on the position in the resonance cavity (optimized for measurements of magnetic dipole transitions) suggests the microwave electric field-driven cyclotron resonance. Cyclotron resonance-related lines are commonly detected in ESR cavities both in bulk materials 24 as well as in 2D systems like Si/SiGe quantum wells 25 or GaN/AlGaN heterostructures. 19 We should mention here that the signal did not show any signs of aging within a time scale of a month.…”
mentioning
confidence: 99%
“…In our experiment, the cyclotron resonance (CR) of the electrons in the quantum well is also observed [4,5]. From the CR signal the carrier concentration and the electron mobility can be estimated.…”
Section: Resultsmentioning
confidence: 92%